2005
DOI: 10.1038/sj.gene.6364170
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin 17F gene (IL17F) and asthma

Abstract: Interleukin17F (IL17F) is a regulatory cytokine for T-cell-mediated immune responses. The gene coding for IL17F (IL17F) is located on chromosome 6p, a genomic region linked to asthma and asthma-related phenotypes in multiple genome scans. IL17F is expressed in lung tissue, in bronchoalveolar lavage fluid from asthmatic subjects, and in activated CD4 þ cells. We were thus interested in testing for association between single-nucleotide polymorphisms (SNPs) and haplotypes in IL17F and asthma. To characterize poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
(31 reference statements)
1
36
0
Order By: Relevance
“…In addition, it has been shown that this variant is functional in vivo, and that it influences asthma susceptibility. The other study by Ramsey et al, using 1027 Caucasian female subjects, found no association between asthma and IL-17F polymorphisms [28]. This discrepancy may be a result of the facts that the frequency of IL-17F/7488C allele was lower in the European American subjects (4.5%) than in the healthy Japanese subjects (11.4%).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, it has been shown that this variant is functional in vivo, and that it influences asthma susceptibility. The other study by Ramsey et al, using 1027 Caucasian female subjects, found no association between asthma and IL-17F polymorphisms [28]. This discrepancy may be a result of the facts that the frequency of IL-17F/7488C allele was lower in the European American subjects (4.5%) than in the healthy Japanese subjects (11.4%).…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study by Ramsey et al, 18 relationships between asthma and IL17F polymorphisms (including the H161R variant) were examined using 1027 white female subjects. The study found no associations between asthma and IL17F polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…A negative association between the rs763780 SNP and atopic dermatitis or psoriasis vulgaris was reported in a Japanese population [14]. Ramsey et al [9] failed to find any association between polymorphisms of the IL-17F gene and asthma. In contrast, however, Kawaguchi et al [10] found a positive association between the rs763780 SNP in exon 3 and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A number of polymorphisms in the IL-17F gene have recently been identified in an African American group, a European American group and a Japanese group [9,10]. Furthermore, association studies between IL-17F polymorphisms and asthma have been conducted in these groups.…”
Section: Discussionmentioning
confidence: 99%